Green fabricated MgO nanoparticles as antimicrobial agent: Characterization and evaluation. (2021) - Vidhya, E.; Vijayakumar, S.; Nilavukkarasi, M.; Punitha, V.N.; Snega, S.; Praseetha, P.K.
Abstract: The represented study is concerned with the production of MgO nanoparticles using Ocimum americanum aqueous extract is an environment friendly and economic method. The facial method of MgO nanoparticles have been confirmed using UV–Visible spectroscopy, FTIR, XRD, FESEM with EDAX respectively. Agar well digging method helped to analyze the antimicrobial evolution against skin disease causing pathogenic organisms like Bacillus cereus, Clostridium perfringens, Klebsiella pneumonia, Salmonella paratyphi, Candida albicans, and Aspergillus niger. The XRD analysis confirms the polycrystalline cubic structure with 42 nm size of the nanoparticles which was further verified by the Debye-Scherrer's formula. Through FESEM analysis, the structure of the nanoparticles was observed to be spherical. Green synthesized MgO nanoparticles were found to be assuring excellent antimicrobial agents against pathogenic microorganisms. Based on the results, green synthesis of MgO nanoparticles has potential applications in the field of medical sectors. Therefore, this type of biosynthesis could be enhanced for huge level preparation of MgO nanoparticles.